2021
DOI: 10.1016/j.cnp.2021.02.006
|View full text |Cite
|
Sign up to set email alerts
|

24-Hour video EEG in the evaluation of the first unprovoked seizure

Abstract: Highlights In the evaluation of a first seizure, the capture of epileptiform discharges is increased with 24-hour EEG recordings. This likely stems from a combination of increased sampling and robust sleep recording. Subtle seizures were also recorded by prolonging the EEG in a minority of first seizure presentations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In this study, treatment initiation after the first versus the second seizure was not associated with a worse long‐term prognosis [3]. Moreover, several previous large‐scale studies have shown that prior seizures are a risk factor for seizure relapse in NOE [3–5]. Seizure recurrence remained different up to 8 years if patients had experienced previous (untreated) seizures, independent of whether immediate or deferred treatment was offered [3].…”
Section: Introductionmentioning
confidence: 84%
“…In this study, treatment initiation after the first versus the second seizure was not associated with a worse long‐term prognosis [3]. Moreover, several previous large‐scale studies have shown that prior seizures are a risk factor for seizure relapse in NOE [3–5]. Seizure recurrence remained different up to 8 years if patients had experienced previous (untreated) seizures, independent of whether immediate or deferred treatment was offered [3].…”
Section: Introductionmentioning
confidence: 84%